Identifying regulators of synaptic stability during normal healthy ageing - Graham, Laura Caroline (The University of Edinburgh, 2018)
The loss and dysfunction of selected populations of synapses is characteristic of mammalian brain ageing and alterations in these receptive compartments are considered to underpin age-related cognitive decline. Discrete neuro-anatomical regions of the cortical architecture harbour disparate populations of synapses that demonstrate significant heterogeneity with regards to advancing age. Of particular interest is the hippocampus, which is selectively vulnerable during ageing. The hippocampal synaptic architecture exhibits subtle structural and biophysical alterations, which are considered to promote the manifestation of cognitive symptoms in aged patients. This notion of “selective synaptic vulnerability” has been the focal point of a multitude of morphological studies investigating age-related cognitive decline, which have often provided tentative conclusions as to how this phenomenon may be regulated. The molecular correlates bolstering the reported age-dependent morphological and functional shift remain elusive and studies are only now beginning to unravel how discrete organelles, proteins and signalling cascades may hierarchically or synergistically attenuate synaptic function. Until there is considerable comprehension of how functional mediators drive the biochemical substrates regulating age-related cognitive decline, there are limited strategic avenues for the development of efficacious therapeutic interventions that promote successful ageing. To address the phenomenon of selective synaptic vulnerability, we have utilised an unbiased combinatorial approach, including quantitative proteomic analyses coupled with in vivo candidate assessments in lower order animals (Drosophila), to temporally profile regional synapse and synaptic mitochondrial biochemistry during normal healthy ageing. We begin by demonstrating that cortical mitochondria located at the synaptic terminal are morphologically distinct from non-synaptic mitochondria in adult rodents and human patients. Biochemical isolation and purification of discrete mitochondrial subpopulations from control adult rat fore-brain enabled generation of synaptic and non-synaptic mitochondrial molecular fingerprints using quantitative proteomics, which revealed that expression of the mitochondrial proteome is highly dependent on subcellular localisation. We subsequently demonstrate that the molecular differences observed between mitochondrial sub-populations are capable of selectively influencing synaptic morphology in-vivo. Next, we sought to examine how the synaptic mitochondrial proteome was dynamically and temporally regulated throughout ageing to determine whether protein expression changes within the mitochondrial milieu are actively regulating the age-dependent vulnerability of the synaptic compartment. Proteomic profiling of wild-type mouse cortical synaptic and non-synaptic mitochondria across the lifespan revealed significant age-dependent heterogeneity between mitochondrial subpopulations, with aged organelles exhibiting unique protein expression profiles. Recapitulation of aged synaptic mitochondrial protein expression at the Drosophila neuromuscular junction has the propensity to perturb the synaptic architecture, demonstrating that temporal regulation of the mitochondrial proteome may directly modulate the stability of the synapse in vivo. Although we had comprehensively characterised the temporal regulation of rodent cortical mitochondrial subpopulations, providing a number of novel candidates that may be mediating synaptic vulnerability during ageing, we sought to establish whether similar alterations were occurring in the primate brain. Using synaptic isolates from neuroanatomically distinct age-resistant (occipital cortex) and age-vulnerable (hippocampus) regions, we demonstrate that synaptic ageing is brainregion dependent and that discrete populations of synapses significantly differ at a biochemical level in the healthy human and non-human primate brain. Recapitulation of aged hippocampal protein expression with genetic manipulation in vivo revealed numerous novel candidates that have the propensity to significantly modulate multiple morphological parameters at the synapse. Furthermore, we demonstrate that several of these candidates sit downstream of TGFβ1 and activation of the TGFβ1 signalling cascade in hippocampal synaptic populations drives the aberrant expression of selected candidates during ageing. Finally, we show that selective pharmacological inhibition of this pathway rescues synaptic phenotypes in multiple candidate lines. The data affirmed that activation of the TGFβ1 transduction pathway modulates synaptic stability and thus may contribute to the selective vulnerability of hippocampal synapses during ageing.
Keywords: ageing; synaptic alterations; hippocampus; synaptic vulnerability